Ichúmar: da errância à música como resistência cultural Kel Tamacheque (1980-2010): raízes históricas e produção contemporânea - Adnane, Mahfouz Ag (2014)
This work aims to offer a reflection on the history of the Kel Tamasheq through an analysis of the context and production of Malian and Nigerien Ichúmar youth musical groups and their experiences of migration andinsile, social and economic marginalization, and political exile. Techúmara is the movement of cultural resistance that arose around the mid-1980s. Nevertheless, such a movement needs to be understood in its roots in the political and economic histories that emerged. Tamasheq youth are undergoing a strong and accelerated process of change and of economic loss and loss of freedom. The main objective, therefore, is to analyze the production of Tamasheq music, articulated within the context of political action and the social and cultural developments that emerged from the conflict between society and the State to 1) establish a corpus from the discography of songs produced by the Ichúmar Movement (1980-2010) such as written poetry of resistance; 2 ) discuss the relationship between the corpus of musical text-literary production-of the Ichúmar generation, taking into consideration the historical events, and analyze the themes present in this form of cultural expression. The music is a hybrid expression and cultural form that is strongly open to influences, especially given the context of nomadism and exile. As a unique style, produced in confluence with Western, Arab, and Tamasheq music, Ichúmar music is an expression that is intensely inscribed in the present and in contemporary mobility. The text (musical poetry set to the lyrics of songs) that is produced within this literary form is the result of a complex process in which the imaginary and the real are profoundly interwoven in the effort to narrate the events (social, political, aesthetic, emotional, identity-related) that involve various dimensions of the human experience. The experience turns the guitar, the fundamental instrument of the rockers of Tenere (the desert), into a footbridge for communication that is at once internal and rooted (to raise awareness among young people and get them to join the struggle) and innovative and external, to raise awareness and make their causes known beyond the borders of this ancient Saharan society